1965
DOI: 10.2118/894-pa
|View full text |Cite
|
Sign up to set email alerts
|

A Correlation for Predicting Water Coning Time

Abstract: This paper presents a correlation for predicting the behavior of a water cone as it builds from the static water-oil contact to breakthrough conditions. The correlation is partly empirical and involves dimensionless groups of reservoir and fluid properties and of production and well characteristics. The groups were deduced from the scaling criteria for the immiscible displacement of oil by water. The correlation is based on a limited amount of experimental data from a laboratory, sand-packed model and on resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 0 publications
0
30
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] The effect of finitewellbore conductivity on coning behavior and breakthrough time, however, is yet to be investigated in sufficient detail. In this study, we present an approximate analytical model to predict the behavior of an evolving cone and its breakthrough into a finite-conductivity horizontal well.…”
Section: Spe 60308mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] The effect of finitewellbore conductivity on coning behavior and breakthrough time, however, is yet to be investigated in sufficient detail. In this study, we present an approximate analytical model to predict the behavior of an evolving cone and its breakthrough into a finite-conductivity horizontal well.…”
Section: Spe 60308mentioning
confidence: 99%
“…The water breakthrough time for this case, calculated using Sobocinski's model [16], is 387 days for an oil production rate of 50 bbl/day, and 191 days for an oil production rate of 80 bbl/day. This means that after 315 days of oil production at a rate of 50 bbl/day, the slowly developing water cone almost reached the oil perforations.…”
Section: Comparison With Actual Production Rate Case Historymentioning
confidence: 99%
“…Sobocinski and Cornelins [16) developed correlations for predicting the behavior of a water cone as it builds from the static water-oil contact to breakthrough. They noted that the previous analyses of critical production rate disregarded the effect of time required for a cone to build up just before its breakthrough.…”
mentioning
confidence: 99%
“…Typically, these studies were aimed at determining critical rates t-s or/and breakthrough times .. 6 • 7~ Coning reversal has not been considered in these studies because of a very long time required for the reversal. Recent results published by Butler and Jiang 8 showed that time required for water cone to return to the initial conditions after the well is shutdown is greater than 3.5 years.…”
Section: Introductionmentioning
confidence: 99%